2010
DOI: 10.1002/hup.1139
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of 5‐hydroxytryptophan (5‐HTP) impairs decision making under ambiguity but not under risk: evidence from the Iowa Gambling Task

Abstract: Oral 5-HTP is psychoactive at low doses. Decisions made under ambiguity may be differentially sensitive to increased serotonin release or associated reductions in frontocortical dopamine activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…In our relatively large sample, the mean probability of choosing a card from the “good” decks was below 50% for trials 1–19 and above 50% for all of the remaining 80 trials (i.e., trial 19 = 45% and trial 20 = 56%). Recent studies are consistent with this characterization as trials 1–20 representing ambiguity and trials 41–100 representing risk (Brand et al, 2007b;Gendle and Golding, 2010; Stoltenberg and Vandever, 2010). …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In our relatively large sample, the mean probability of choosing a card from the “good” decks was below 50% for trials 1–19 and above 50% for all of the remaining 80 trials (i.e., trial 19 = 45% and trial 20 = 56%). Recent studies are consistent with this characterization as trials 1–20 representing ambiguity and trials 41–100 representing risk (Brand et al, 2007b;Gendle and Golding, 2010; Stoltenberg and Vandever, 2010). …”
Section: Discussionmentioning
confidence: 56%
“…There is some controversy regarding how much participants know about the response contingencies of each deck and when they know it (Brand et al, 2006). Although consensus has not yet been reached on how to define these two phases of decision making, emerging evidence suggests that at least in healthy adults only the first 20 trials should be considered ambiguity (Gendle and Golding, 2010; Stoltenberg and Vandever, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that 5-HT plays a key role during top-down control of decision-making (Van den Bos et al 2013) but some authors found that a low level of extracellular 5-HT is linked with poor performance during decision-making (Heitland et al 2012; Homberg et al 2008; Koot et al 2012; Pittaras et al 2013; Zeeb et al 2009) while others did not (Gendle et al 2010; Homberg et al 2008; Lage et al 2011; Macoveanu et al 2013; Stoltenberg et al 2011). Here, we observed that risky mice had a high level of 5-HT in the prelimbic (PrL), insular cortices (CIns) and a low level of 5-HT in the orbitofrontal cortex (OFC).…”
Section: Discussionmentioning
confidence: 99%
“…The COMT (catechol- O -methyltransferase) gene polymorphism leading to an increased level of endogenous dopamine, and serotonin transporter (5-HTTLPR) polymorphisms have been associated to decision-making impairments (Heitland et al 2012; Homberg et al 2008; Malloy-Diniz et al 2013). However, the results concerning 5-HT are somewhat contradictory (Gendle and Golding 2010; Heitland et al 2012; Homberg et al 2008; Koot et al 2012; Lage et al 2011; Macoveanu et al 2013; Pittaras et al 2013; Stoltenberg et al 2011; Zeeb et al 2009). …”
Section: Introductionmentioning
confidence: 99%